2012
DOI: 10.1136/bmj.e7085
|View full text |Cite
|
Sign up to set email alerts
|

Risks of adverse pregnancy and birth outcomes in women treated or not treated with mood stabilisers for bipolar disorder: population based cohort study

Abstract: Objective To investigate the risks of adverse pregnancy and birth outcomes for treated and untreated bipolar disorder during pregnancy.Design Population based cohort study using data from national health registers. Setting Sweden.Participants 332 137 women with a last menstrual period anytime after 1 July 2005 and giving birth anytime before the end of 31 December 2009. Women with a record of at least two bipolar diagnoses were identified and grouped as treated (n=320)-those who had filled a prescription for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 33 publications
3
137
1
2
Order By: Relevance
“…The issues most frequently raised are fear of adverse effects of medications on the fetus, fear of illness recurrence, and genetic transmission to offspring 507. Other important topics to review include the effect of BD on risk for gestational hypertension, antepartum haemorrhage, induction of labour, caesarean section, instrumental delivery, preterm delivery, and neonatal size 508, 509. Discussion of modifiable risk factors is critical in pre‐conception management of BD.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issues most frequently raised are fear of adverse effects of medications on the fetus, fear of illness recurrence, and genetic transmission to offspring 507. Other important topics to review include the effect of BD on risk for gestational hypertension, antepartum haemorrhage, induction of labour, caesarean section, instrumental delivery, preterm delivery, and neonatal size 508, 509. Discussion of modifiable risk factors is critical in pre‐conception management of BD.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Discussion of modifiable risk factors is critical in pre‐conception management of BD. For instance, pregnant women with BD are more often overweight, more often smoke tobacco during pregnancy, have poorer diet quality, and present more often with a history of drug and alcohol misuse in pregnancy 509. Modification of these risk factors may have a significant positive impact on outcomes for both the mother and child.…”
Section: Specific Populationsmentioning
confidence: 99%
“…71 Pilo et al 71 demonstrated a higher rate of children born with respiratory distress (odds ratio 2.06, 95% CI 1.62 to 2.63). Another Swedish study 112 also based on national health registries demonstrated that women with bipolar disorder treated with psychotropic medication (anticonvulsant mood stabilisers, lithium or antipsychotics) were more likely to experience caesarean section and preterm delivery. Discontinuation and factors associated with continuation of psychotropic medication in pregnancy l The overall patterns of discontinuation of psychotropic medication were remarkably similar between classes of psychotropic medication.…”
Section: Anticonvulsant Mood Stabilisersmentioning
confidence: 99%
“…[19][20][21] Furthermore, the negative impact of maternal mental illness on child development and child psychopathology is substantial. [22][23][24] Given that adolescents are at high risk of adverse pregnancy outcomes, children of adolescent mothers with mental illness may be "doubly" vulnerable due to the independent risks associated with being the child of both an adolescent and a woman with a major mental illness.…”
Section: Discussionmentioning
confidence: 99%